2016
DOI: 10.1093/jjco/hyw069
|View full text |Cite
|
Sign up to set email alerts
|

Fertility-sparing surgery for early stage epithelial ovarian cancer

Abstract: Discussion of fertility-sparing treatment is an important part of pretreatment counseling for young patients with early epithelial ovarian cancer. As a result of late childbearing nowadays, fertility preservation has become a major issue in ovarian cancer patients. The purpose of this review is to update current knowledge on fertility-sparing treatment for early stage epithelial ovarian cancer, which may be useful for pretreatment counseling for reproductive-age patients. The multicenter study data on the fert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 42 publications
(74 reference statements)
2
16
0
Order By: Relevance
“…In both the SEER and NCDB cohorts, FSS was unrelated to survival in subgroups defined by stage and grade, and these findings are in line with other single‐institution, retrospective studies . Previously published studies have reported that high‐grade tumors should not be considered for FSS because of an increased risk of recurrence; however, the inclusion of stage and grade concurrently in the analyses is inconsistent …”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In both the SEER and NCDB cohorts, FSS was unrelated to survival in subgroups defined by stage and grade, and these findings are in line with other single‐institution, retrospective studies . Previously published studies have reported that high‐grade tumors should not be considered for FSS because of an increased risk of recurrence; however, the inclusion of stage and grade concurrently in the analyses is inconsistent …”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, we noted an elevated but not statistically significant risk of death among women with stage IC disease of either serous or endometrioid histology. Others have noted increased risks associated with FSS in these subgroups, 7,[20][21][22] and this supports the recommendation that FSS in these clinical scenarios should be considered on a case-by-case basis with thorough patient counseling. It should be noted that the sample sizes within tumor categories were relatively low; therefore, whether our results indicate the safety of FSS or underpowered analyses is unclear, and additional studies are warranted.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…8,12 In these patients, the recurrencefree and overall survival rates are estimated to be 93.4% and 98.0%, respectively, without adjuvant chemotherapy. 47 FSS has also been suggested to be reasonable in stage IC disease, albeit slightly increased recurrence rates. A systematic review that included data from 1110 women with stage I EOC reported recurrence rates of 10% for stage IA disease and 16% for stage IC disease following FSS.…”
Section: Cancer Stagementioning
confidence: 99%
“…In a conglomerate patient population with stage I grade 3 EOC from several published studies on FSS, the recurrence rate was 46% and survival rate was 68% in a total of 37 patients, which were significantly lower than those respective rates for grade 1-2 diseases. 17,28,47,53 In another study specifically evaluating characteristics and survival outcomes of recurrent EOC after FSS in 81 patients with grade 3 disease, 23.5% had recurrent disease, and 95% of the recurrences were extraovarian. Only 22% of these extraovarian recurrences achieved disease-free status, confirming the aggressive nature of these poorly differentiated tumors.…”
Section: Cancer Stagementioning
confidence: 99%